Knowledge, Nature, and the Good : Essays on Ancient Philosophy - Cooper, John M. (John Madison), 1939- (Book collections on Project MUSE., 2004)
Knowledge, Nature, and the Good brings together some of John Cooper's most important works on ancient philosophy. In thirteen chapters that represent an ideal companion to the author's influential Reason and Emotion, Cooper addresses a wide range of topics and periods--from Hippocratic medical theory and Plato's epistemology and moral philosophy, to Aristotle's physics and metaphysics, academic scepticism, and the cosmology, moral psychology, and ethical theory of the ancient Stoics. Almost half of the pieces appear here for the first time or are presented in newly expanded, extensively revised versions. --From publisher's description.